Kawalan Inflasi Pengurusan Risiko dan Kitaran Ekonomi (Economic Cycle) Dalam Sistem Perbankan Islam di Malaysia - Sulaiman, A. A.; Shuib, M. S.; Mohamad, M. T. (Universiti Sains Islam Malaysia, 2024)
The Implementation of Islamic Banking System in Malaysia since 1983 are now entering the phase of liberalization. This research is to measure and identify the extent to which changes in the rate of inflation, risk management and economic cycles affect the performance of Malaysian Islamic banking system in Malaysia during the period of 14 years from 1994 to 2008. To meet the objectives of the study, analysis of panel data estimation (panel data regression) was performed to assess the extent to which the relationship and influence of each factor on the performance of Islamic Banking System in Malaysia.